The impact of self-esteem on the playing activity of skilled hockey players - Валентина Воронова; Надежда Высочина; Андрей Михнов (National University of Physical Education and Sport of Ukraine, 2017)
It was theoretically proved that self-esteem is one of the most significant parameters of the athlete's personality, because it stimulates the increase in the effectiveness of competitive activity and plays the role of its regulator. The main directions for studying the self-esteem of high class hockey players were identified. Based on the results of the expert survey, the structure of the analysis of the self-esteem of high class hockey players was determined. Three blocks of indicators were distinguished in the structure of self-esteem: the self-assessment of the level of physical fitness and health, the self-assessment of the level of technical and tactical preparation, and the self-assessment of the level of psychological preparation. The analysis of the self-esteem of high-class hockey players was carried out using the scales related to various aspects of preparation (physical, technical and tactical, and psychological), which revealed both the individual level of the demonstration of self-esteem of players and the mean group values that allowed to determine the most significant components in the overall structure of self-esteem of hockey players. Integral indicators of the self-esteem of hockey players that affect their playing activity were identified and analyzed along with the relationships between them. It was shown that high-class hockey players show a direct correlation between the level of the self-esteem and the results of competitive activity, furthermore, a high level of self-esteem can positively influence the success of their performances.